Pengaruh Ukuran Perusahaan, Struktur Aset, Pertumbuhan Penjualan, Profitabilitas dan Current Ratio terhadap Struktur Modal Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia - Bayu Wulandari; Veronika Marsaulina Lumbantoruan Lumbantoruan; Jelita Wanna Naibaho; Winna Regina; R. Chairuddin Zufriansyah; Frenki Okto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The amount of assets owned by the company is the value of the size of the company. This study aims to test whether company size, asset structure, sales growth, profitability and current ratio have an influence on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (BEI). This type of research is quantitative descriptive, using 144 manufacturing companies listed on the IDX. This study uses a sampling method, namely purposive sampling and has obtained as many as 216 samples. This study uses data in the form of annual financial reports from each sample company published on the website www.idx.co.id. The variables related to this study are company size, asset structure, profitability, sales growth, and current ratio. The research method used is descriptive method and multiple linear regression analysis method. The results showed that Company Size, Asset Structure, Profitability and Current Ratio had no significant effect on capital structure. Meanwhile, sales growth has a significant effect on the capital structure. Simultaneously, Company Size, Asset Structure, Profitability, Sales Growth and Current Ratio together have a significant and significant effect on the company's capital structure as measured by the capital structure listed on the IDX. Keywords: Company Size, Asset Structure, Sales Growth, Profitability, Current Ratio, and Capital Structure.